The Effect of Leverage and Capital Intensity on Tax Avoidance (Empirical Study on Primary Consumer Goods Sector Companies Listed on the Indonesia Stock Exchange for the Period 2020–2024) - Nuraini Nuraini; Titah Rahmawati (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of leverage and capital intensity on tax avoidance in companies operating within the primary consumer goods sector listed on the Indonesia Stock Exchange. The research employs a quantitative approach using secondary data obtained from annual financial reports. The sample was selected using a purposive sampling technique based on predetermined criteria. The analysis was conducted using panel data regression with the assistance of EViews software. The findings show that leverage has a significant and positive effect on tax avoidance, indicating that firms with higher debt ratios tend to engage more actively in minimizing their tax burden. Conversely, capital intensity does not have a significant influence on tax avoidance, suggesting that investment in fixed assets does not necessarily correlate with corporate tax-saving behavior. This study provides important insights for both practitioners and regulators in understanding the financial strategies related to tax planning in Indonesia's consumer goods industry.